2003
DOI: 10.1021/jo0346306
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of New Cyclic Thionosulfites

Abstract: The reaction of a series of 1,2-diols with S(2)Cl(2), 1,1'-thiobisbenzimidazole (4a), and 1,1'-dithiobisbenzimidazole (4b) provides the corresponding thionosulfites, ROS(S)OR (2), in moderate to good yield.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
10
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Since then, the work conducted generally has been for a specific subset of compounds 4-14 or for theoretical investigations. [15][16][17][18] Although compounds of form 2 have been characterized, [19][20][21][22] the only known systems with this thionosulfite moiety are cyclic. [20][21][22] Compounds containing the OSSO fragment 1 possibly isomerize into their valence-bond isomeric thionosulfite form (OS(dS)O 2).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Since then, the work conducted generally has been for a specific subset of compounds 4-14 or for theoretical investigations. [15][16][17][18] Although compounds of form 2 have been characterized, [19][20][21][22] the only known systems with this thionosulfite moiety are cyclic. [20][21][22] Compounds containing the OSSO fragment 1 possibly isomerize into their valence-bond isomeric thionosulfite form (OS(dS)O 2).…”
mentioning
confidence: 99%
“…[15][16][17][18] Although compounds of form 2 have been characterized, [19][20][21][22] the only known systems with this thionosulfite moiety are cyclic. [20][21][22] Compounds containing the OSSO fragment 1 possibly isomerize into their valence-bond isomeric thionosulfite form (OS(dS)O 2). 23 5964…”
mentioning
confidence: 99%
“…Dialkoxy disulfides were first synthesized in the late 19 th century by Lengfeld [1], however they lay in relative obscurity until the 1990's when Harpp and others began to examine this novel structural moiety [2][3][4][5][6][7][8][9][10][11][12][13][14][15]. Although examples of the isomeric form, thionosulfite (-OS(=S)O-) have been reported, however only in cyclic structures [3,12], the predominate form is believed to be the linear arrangement, (-OSSO-).…”
Section: Introductionmentioning
confidence: 99%
“…Although examples of the isomeric form, thionosulfite (-OS(=S)O-) have been reported, however only in cyclic structures [3,12], the predominate form is believed to be the linear arrangement, (-OSSO-). It was revealed that dialkoxy disulfidescould act as an S 2 donating group in pseudo-Diels Alder reactions [8,11].…”
Section: Introductionmentioning
confidence: 99%
“…119 A new, reproducible and simple route to cyclic thionosulfites, ROS(S)OR, involves the reaction of 1,2-diols with S 2 Cl 2 and 1,1'-thiobisbenzimidazole or 1,1'dithiobisbenzimidazole. 120 The methodology reports the absence of side-products and the materials can be easily isolated by column chromatography to give yields of up to 80%. A sulfito ligand is responsible for bridging two imidotin cubanes to afford the complex [(SnNt-Bu) 4 m-OSO 2 ] 2 (THF).…”
mentioning
confidence: 99%